Oral ingestion of hexavalent chromium through drinking water and cancer mortality in an industrial area of Greece - An ecological study - Linos, Athena; Petralias, Athanassios; Christoforidou, Eleni; Kouroutou, Paraskevi; Stoltidis, Melina; Veloudaki, Afroditi; Tzala, Evangelia; Karagas, Margaret R.; Makris, Konstantinos C.; Christophi, Costas A. (My University, 2011)
Background: Hexavalent chromium is a known carcinogen when inhaled, but its carcinogenic potential when orally ingested remains controversial. Water contaminated with hexavalent chromium is a worldwide problem, making this a question of significant public health importance. Methods: We conducted an ecological mortality study within the Oinofita region of Greece, where water has been contaminated with hexavalent chromium. We calculated gender, age, and period standardized mortality ratios (SMRs) for all deaths, cancer deaths, and specific cancer types of Oinofita residents over an 11-year period (1999 - 2009), using the greater prefecture of Voiotia as the standard population. Results: A total of 474 deaths were observed. The SMR for all cause mortality was 98 (95% CI 89-107) and for all cancer mortality 114 (95% CI 94-136). The SMR for primary liver cancer was 1104 (95% CI 405-2403, p-value < 0.001). Furthermore, statistically significantly higher SMRs were identified for lung cancer (SMR = 145, 95% CI 100203, p-value = 0.047) and cancer of the kidney and other genitourinary organs among women (SMR = 368, 95% CI 119-858, p-value = 0.025). Elevated SMRs for several other cancers were also noted (lip, oral cavity and pharynx 344, stomach 121, female breast 134, prostate 128, and leukaemias 168), but these did not reach statistical significance. Conclusions: Elevated cancer mortality in the Oinofita area of Greece supports the hypothesis of hexavalent chromium carcinogenicity via the oral ingestion pathway of exposure. Further studies are needed to determine whether this association is causal, and to establish preventive guidelines and public health recommendations.
Keywords: Chromium; Chromates; Potassium Dichromate